Preparation method and application of WS2 / g-C3N5 heterojunction material
The WS2/g-C3N5 heterojunction material was prepared by solvent thermal in situ growth method, which solved the problem of limited photocatalytic performance of a single material, and achieved the improvement of photocatalytic activity and efficient removal of environmental pollutants.
Patent Information
- Application Number
- CN202411866612.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing single WS2 and g-C3N5 materials have problems with narrow light absorption range and high photogenerated charge recombination rate in the field of photocatalysis, which limits the improvement of their photocatalytic performance.
Through the solvent-thermal in-situ growth method, WS2/g-C3N5 heterojunction material was prepared, and the layered characteristics of the two were used for layer-layer composite, increasing the contact area, enhancing the interface effect, and promoting efficient separation of photogenerated charges and light absorption.
The photocatalytic activity has been significantly improved, especially in removing environmental pollutants such as rhodamine B, methylene blue, methyl orange, etc., which significantly improves the photocatalytic performance of the material.
Smart Images

Figure CN119318983B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of heterojunction photocatalytic materials, and specifically relates to a preparation method and application of a WS2 / g-C3N5 heterojunction material. Background Art
[0002] With the acceleration of industrialization, energy crisis and environmental pollution are becoming increasingly serious, and human society is facing unprecedented challenges. Excessive consumption of fossil fuels has led to energy shortages, and the large amount of greenhouse gases and pollutants produced have caused serious damage to the environment. In this context, it is particularly important to develop new and efficient energy conversion and environmental purification technologies. Chemical oxidation, especially photocatalytic technology, has attracted much attention due to its significant advantages in the field of environmental purification and energy conversion.
[0003] Photocatalytic technology uses light energy to excite catalysts to produce active species that can promote chemical reactions, such as hydroxyl radicals (·OH) and superoxide anions (·O2 - ), these active species can effectively degrade organic pollutants, reduce heavy metal ions, and even decompose water to produce hydrogen. Compared with traditional thermal catalysis and chemical oxidation, photocatalysis technology has the advantages of mild reaction conditions, low energy consumption, and no secondary pollution. Especially in the use of solar energy, photocatalysis technology has shown great potential and is considered to be one of the effective means to solve energy and environmental problems.
[0004] Among many photocatalytic materials, heterojunction photocatalytic materials have attracted much attention due to their unique electronic structure and interface effects. Heterojunction materials can effectively promote the separation and migration of photogenerated charges by constructing interfaces between different components, thereby improving the photocatalytic efficiency. Among them, two-dimensional materials such as g-C3N5 have become a hot topic of research due to their unique electronic structure and optical properties. Tungsten disulfide (WS2) is also a new type of photocatalyst. It has a "sandwich" layered structure in which a tungsten atomic layer is sandwiched between two layers of sulfur atoms. This structure gives WS2 unique electronic properties. For example, bulk WS2 is usually an indirect bandgap semiconductor, but when stripped into a single layer, it is transformed into a direct bandgap semiconductor. The bandgap width can be adjusted by controlling the number of stripped layers. In addition, WS2 also has a wide spectral response and high light absorptivity. It can absorb light from the ultraviolet to the near-infrared region, and also exhibits excellent saturated light absorptivity, which enables it to more efficiently utilize light energy in photocatalytic reactions.
[0005] However, whether it is g-C3N5 or WS2, single materials often have problems such as narrow light absorption range and high photogenerated charge recombination rate, which limits the further improvement of their photocatalytic performance.
[0006] In response to these problems, the design of new heterojunction photocatalytic materials is particularly critical. Professor Liu Bin's team from Shanxi University (DOI: 10.1080 / 09276440.2022.2076363) doped a small amount of CdS precursor into the prepared porous C3N5 precursor and synthesized CdS / C3N5 compounds by hydrothermal method. Compared with C3N5, the absorption range of CdS / C3N5 material is slightly reduced, but the carrier mobility is increased. Through the type I heterojunction, the electron-hole recombination rate is greatly reduced, thereby improving the photocatalytic performance. The Jingjiang team of Chengdu University of Science and Technology (DOI: 10.1016 / j.envres.2023.116939) used a hydrothermal in situ synthesis method to construct a new FeS2 / CN heterojunction material based on g-C3N5, and successfully activated sulfite, with a degradation rate of 96% for tetracycline within 1 hour. The FeS2 / CN heterostructure enhances the absorption of visible light and suppresses the recombination of carriers, thereby making it possible to utilize more electrons and holes. Chinese patent ZL 202410104813.9 proposes a method of anchoring WS2 with rare earth La and composite WO 3-x The construction of heterojunction photocatalytic materials solves the problem of low catalytic activity caused by the rapid recombination of photogenerated carriers in the photocatalytic process of traditional WO3 materials, thereby improving the activity of photocatalytic nitrogen conversion to product ammonia. Chinese patent ZL202210272095.7 provides a WS2 / MoS2 two-dimensional coherent heterojunction network material and a preparation method thereof. By chemical vapor deposition, a single MoTe2 layer of the 2H phase is subjected to a sulfurization reaction to obtain a sulfurized product, and the sulfurized product is reacted with a tungsten source and sulfur powder to grow to obtain the WS2 / MoS2, a two-dimensional coherent heterojunction network material. This method is simple to operate, has high repeatability, a large structural area, and low cost, and fills the current technical gap in the uncontrollable small area of the two-dimensional coherent heterojunction growth, which is of significant significance.
[0007] However, to date, there has been no report on the materials, preparation methods and applications of the composite of WS2 and g-C3N5 to construct WS2 / g-C3N5.
[0008] In view of the above background and research status, the present invention is proposed. Summary of the invention
[0009] The purpose of the present invention is to provide a method for preparing a WS2 / g-C3N5 heterojunction material, which is in-situ grown in a solvent-thermal manner, and not only is the preparation process simple, but also the interface of the heterojunction material obtained by in-situ growth is tightly bonded. By utilizing the layered characteristics of WS2 and g-C3N5, the contact area between the two is increased to the greatest extent through layer-by-layer compounding, the transmission channel of photogenerated carriers is strengthened through the interface effect, and the efficient separation of photogenerated electrons and holes is promoted. At the same time, the wide spectral response range and saturated light absorption rate of WS2 are utilized to enhance the efficient absorption of sunlight by the heterojunction material, and finally a significant improvement in photocatalytic activity is achieved.
[0010] Another object of the present invention is to provide a WS2 / g-C3N5 heterojunction material for use in fields such as removal of environmental pollutants.
[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0012] In a first aspect, the present invention provides a method for preparing a WS2 / g-C3N5 heterojunction material, comprising the following steps:
[0013] (1) Weigh 3-amino-1,2,4-triazole into a crucible and calcine in a muffle furnace to obtain g-C3N5;
[0014] (2) Weigh WCl6 and add it to anhydrous ethanol. After stirring until all the solids are dissolved, add a sulfur source, hexadecyltrimethylammonium bromide, and the g-C3N5 obtained in step (1). After stirring, transfer the mixture into a hydrothermal reactor for reaction. After washing, the product is obtained to obtain a WS2 / g-C3N5 heterojunction material.
[0015] The molar ratio of sulfur element to WCl6 in the sulfur source is 3:1.
[0016] The mass concentration of the hexadecyltrimethylammonium bromide in anhydrous ethanol is 5-20 mg / mL.
[0017] The sulfur source is at least one of thioacetamide and thiourea.
[0018] In some embodiments, the calcination temperature of the muffle furnace is 520° C., and the calcination time is 3 hours.
[0019] In some embodiments, the reaction temperature of the hydrothermal reactor is 120 to 200° C., and the reaction time is 12 to 48 hours.
[0020] In a second aspect, the present invention provides an application of the WS2 / g-C3N5 heterojunction material prepared by the above-mentioned preparation method in the field of removing environmental pollutants.
[0021] The environmental pollutant includes at least one of rhodamine B, methylene blue, and methyl orange dyes.
[0022] As a preferred embodiment, a method for preparing a WS2 / g-C3N5 heterojunction material comprises the following steps: (1) weighing 3-amino-1,2,4-triazole and adding it into a crucible, and calcining it in a muffle furnace to obtain g-C3N5;
[0023] (2) Weigh WCl6 and add it to anhydrous ethanol. After stirring until all the solids are dissolved, add a sulfur source, hexadecyltrimethylammonium bromide, and the g-C3N5 obtained in step (1). After stirring, transfer the mixture into a hydrothermal reactor for reaction. After washing, the product is obtained to obtain a WS2 / g-C3N5 heterojunction material.
[0024] Wherein, in this step, the molar ratio of sulfur element in the sulfur source to WCl6 is 3:1.
[0025] Wherein, in this step, the mass concentration of hexadecyltrimethylammonium bromide in anhydrous ethanol is 10 mg / mL.
[0026] Wherein, in this step, the sulfur source is thioacetamide.
[0027] Wherein, in this step, the roasting temperature of the muffle furnace is 520° C., and the roasting time is 3 hours.
[0028] Wherein, in this step, the reaction temperature of the hydrothermal kettle is 180° C. and the reaction time is 24 hours.
[0029] The beneficial effects of the technical solution provided by the present invention are as follows: Based on the careful design and maximum optimization of the photocatalyst structure, the present invention adopts solvent thermal in-situ synthesis, the preparation process is simple, and a heterojunction material with a tightly bonded interface can be obtained. By utilizing the significant characteristics of WS2 and g-C3N5 as lamellar materials, a heterojunction material with a maximum contact interface is constructed through the tight bonding of lamellar layers over a large area, and the transmission channel of photogenerated carriers is strengthened through the interface effect, promoting the separation of photogenerated charges. At the same time, the wide spectral response range and saturated light absorption rate of WS2 are utilized to enhance the absorption rate of heterojunction materials to sunlight, and finally achieve a significant improvement in photocatalytic activity, especially in terms of efficient removal of environmental pollutants such as rhodamine B, methylene blue, and methyl orange. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the XRD diagram of the sample obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0033] The reagents and raw materials used in the present invention are shown in Table 1 below:
[0034] Table 1 Reagents and raw materials used in the present invention
[0035]
[0036] Example 1
[0037] Accurately weigh 10 grams of 3-amino-1,2,4-triazole and add it to a crucible, and calcine it at 520°C in a muffle furnace for 3 hours to obtain g-C3N5; weigh 3.96 grams of WCl6 and add it to 70 milliliters of anhydrous ethanol, stir until the solid is completely dissolved, add 2.25 grams of thioacetamide, 0.7 grams of hexadecyltrimethylammonium bromide, and 2.5 grams of g-C3N5 obtained in the above steps, stir and transfer it into a 100 milliliter hydrothermal kettle at 180°C to react for 24 hours. After washing the product with water 3 times and anhydrous ethanol 3 times, dry it in a vacuum drying oven overnight to obtain the WS2 / g-C3N5 heterojunction material.
[0038] 100 mg of the prepared WS2 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L rhodamine B solution, ultrasonically treated for 5 minutes, dark adsorbed for 30 minutes, and then illuminated for 45 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 100%.
[0039] Example 2
[0040] Accurately weigh 10 grams of 3-amino-1,2,4-triazole and add it to a crucible, and calcine it at 520°C in a muffle furnace for 3 hours to obtain g-C3N5; weigh 3.96 grams of WCl6 and add it to 70 milliliters of anhydrous ethanol, stir until the solid is completely dissolved, add 2.25 grams of thioacetamide, 0.7 grams of hexadecyltrimethylammonium bromide, and 2.5 grams of g-C3N5 obtained in the above steps, stir and transfer it into a 100 milliliter hydrothermal kettle at 180°C to react for 24 hours. After washing the product with water 3 times and anhydrous ethanol 3 times, dry it in a vacuum drying oven overnight to obtain the WS2 / g-C3N5 heterojunction material.
[0041] 100 mg of the prepared WS2 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methylene blue solution, ultrasonically treated for 5 minutes, dark adsorbed for 30 minutes, and then illuminated for 45 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 664 nm was measured by a UV-visible spectrophotometer. The degradation rate of methylene blue was calculated to be 100%.
[0042] Example 3
[0043] Accurately weigh 10 grams of 3-amino-1,2,4-triazole and add it to a crucible, and calcine it at 520°C in a muffle furnace for 3 hours to obtain g-C3N5; weigh 3.96 grams of WCl6 and add it to 70 milliliters of anhydrous ethanol, stir until the solid is completely dissolved, add 2.25 grams of thioacetamide, 0.7 grams of hexadecyltrimethylammonium bromide, and 2.5 grams of g-C3N5 obtained in the above steps, stir and transfer it into a 100 milliliter hydrothermal kettle at 180°C to react for 24 hours. After washing the product with water 3 times and anhydrous ethanol 3 times, dry it in a vacuum drying oven overnight to obtain the WS2 / g-C3N5 heterojunction material.
[0044] 100 mg of the prepared WS2 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methyl orange solution, ultrasonically treated for 5 minutes, dark adsorbed for 30 minutes, and then illuminated for 45 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 460 nm was measured by a UV-visible spectrophotometer. The degradation rate of methyl orange was calculated to be 88.4%.
[0045] Example 4
[0046] Accurately weigh 10 grams of 3-amino-1,2,4-triazole and add it to a crucible, and calcine it in a muffle furnace at 520°C for 3 hours to obtain g-C3N5; weigh 3.96 grams of WCl6 and add it to 70 milliliters of anhydrous ethanol, stir until the solid is completely dissolved, add 2.25 grams of thioacetamide, 0.35 grams of hexadecyltrimethylammonium bromide, and 2.5 grams of g-C3N5 obtained in the above steps, stir and transfer it into a 100 milliliter hydrothermal kettle at 120°C to react for 12 hours. After washing the product with water 3 times and anhydrous ethanol 3 times, dry it in a vacuum drying oven overnight to obtain the WS2 / g-C3N5 heterojunction material.
[0047] 100 mg of the prepared WS2 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L rhodamine B solution, ultrasonically treated for 5 minutes, dark adsorbed for 30 minutes, and then illuminated for 45 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 93.2%.
[0048] Example 5
[0049] Accurately weigh 10 grams of 3-amino-1,2,4-triazole and add it to a crucible, and calcine it in a muffle furnace at 520°C for 3 hours to obtain g-C3N5; weigh 3.96 grams of WCl6 and add it to 70 milliliters of anhydrous ethanol, stir until the solid is completely dissolved, add 2.25 grams of thioacetamide, 1.4 grams of hexadecyltrimethylammonium bromide, and 2.5 grams of g-C3N5 obtained in the above steps, stir and transfer it into a 100 milliliter hydrothermal autoclave at 200°C to react for 48 hours. After washing the product with water 3 times and anhydrous ethanol 3 times, dry it in a vacuum drying oven overnight to obtain the WS2 / g-C3N5 heterojunction material.
[0050] 100 mg of the prepared WS2 / g-C3N5 heterojunction material was placed in a beaker containing 100 ml of a 10 mg / L methylene blue solution, ultrasonically treated for 5 minutes, dark adsorbed for 30 minutes, and then illuminated for 45 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 664 nm was measured by a UV-visible spectrophotometer. The degradation rate of methylene blue was calculated to be 90.3%.
[0051] Comparative Example 1
[0052] Accurately weigh 10 grams of 3-amino-1,2,4-triazole and add it to a crucible, and calcine it in a muffle furnace at 520°C for 3 hours to obtain g-C3N5; weigh 3.96 grams of WCl6 and add it to 70 milliliters of anhydrous ethanol, stir until the solid is completely dissolved, add 2.25 grams of thioacetamide and 0.7 grams of hexadecyltrimethylammonium bromide, stir and transfer to a 100 milliliter hydrothermal kettle at 180°C to react for 24 hours. After washing the product with water 3 times and anhydrous ethanol 3 times, dry it in a vacuum drying oven overnight to obtain the WS2 monomer material.
[0053] Take 100 mg of the prepared WS2 monomer and place it in a beaker containing 100 ml of 10 mg / L rhodamine B solution. After ultrasonic treatment for 5 minutes and dark adsorption for 30 minutes, it is illuminated by a 300-watt xenon lamp light source at a distance of 20 cm from the liquid surface for 30 minutes under stirring. After centrifugation, the degraded solution is measured by a UV-visible spectrophotometer at 554 nm. The degradation rate of rhodamine B is calculated to be 46.4%.
[0054] Comparative Example 2
[0055] Accurately weigh 2 g of 3-amino-1,2,4-triazole and calcine it at 520 °C in a muffle furnace for 3 h to obtain g-C3N5 monomer.
[0056] 100 mg of the prepared g-C3N5 monomer was placed in a beaker containing 100 ml of a 10 mg / L rhodamine B solution, subjected to ultrasonic treatment for 2 minutes, dark adsorbed for 30 minutes, and then illuminated for 45 minutes with a 300-W xenon lamp at a distance of 20 cm from the liquid surface under stirring. The degraded solution was centrifuged and its absorbance at 554 nm was measured by a UV-visible spectrophotometer. The degradation rate of rhodamine B was calculated to be 58.5%.
[0057] It can be seen from Comparative Examples 1 and 2 that the degradation effect of the prepared WS2 monomer and g-C3N5 monomer materials on Rhodamine B is significantly lower than that of the WS2 / g-C3N5 heterojunction material under the same conditions. This is mainly because neither the WS2 monomer nor the g-C3N5 monomer material forms a spatial electric field for efficient separation of photogenerated carriers, and the photogenerated electrons and holes have a higher probability of resurrection.
[0058] Characterization of WS2 / g-C3N5 heterojunction materials
[0059] The present invention uses a D8 Advance X-ray diffractometer from Bruker Spectroscopy Instruments of Germany to perform XRD characterization on the WS2 / g-C3N5 heterojunction material prepared in Example 1 of the present invention and the g-C3N5 monomer prepared in Comparative Example 2, and the results are as follows: Figure 1 As shown, the test conditions are: Cu target Kα line, λ=0.15406nm, 2θ is 10°~70°, and the scanning speed is 5(°) / min. Figure 1 The product of Comparative Example 2 is g-C3N5, and the diffraction peaks at 2θ of 12.8° and 27.3° correspond to the (100) and (002) crystal planes, respectively. Figure 1 The product of Example 1 is WS2 / g-C3N5. The above two characteristic peaks are both reflected in the spectrum of the product, but the intensity is relatively low, which is mainly due to the non-crystalline structure of g-C3N5 and the stronger diffraction peak of WS2. For WS2, the position of its diffraction peaks corresponds to PDF card 84-1398, and the diffraction peaks at 2θ of 14.4, 28.9, 32.8, 33.6, 26.9, 39.6, 44.1, 44.3, 49.8, 56.0, 58.5, 60.0, 60.6, 62.7, 66.6, 68.7° and 69.1° correspond to the (002), (004), (100), (101), (102), (103), (006), (104), (105), (106), (110), (008), (112), (107), (114), (200) and (201) crystal planes of WS2, respectively. The positions of all peaks in the figure correspond well and the peak lines are sharp, indicating that the prepared samples have high purity.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a WS2 / g-C3N5 heterojunction material, characterized in that: The steps include: (1) Weigh 3-amino-1,2,4-triazole into a crucible and calcine in a muffle furnace to obtain g-C3N5; (2) Weigh WCl6 and add it to anhydrous ethanol. Stir until all the solid is dissolved. Then add a sulfur source, hexadecyltrimethylammonium bromide, and the g-C3N5 obtained in step (1). After stirring, transfer the mixture into a hydrothermal reactor for reaction. After washing, the product is subjected to WS2 / g-C3N5 heterojunction material. Among them, the molar ratio of sulfur element to WCl6 in the sulfur source is 3:1; the mass concentration of hexadecyltrimethylammonium bromide in anhydrous ethanol is 5-20 mg / mL; the roasting temperature of the muffle furnace is 520°C, and the roasting time is 3 hours; the reaction temperature of the hydrothermal autoclave is 120-200°C, and the reaction time is 12-48 hours.
2. The preparation method according to claim 1, characterized in that: The sulfur source is at least one of thioacetamide and thiourea.
3. Application of a WS2 / g-C3N5 heterojunction material obtained by the preparation method described in any one of claims 1 to 2 in removing environmental pollutants.
4. The use according to claim 3, characterized in that: The environmental pollutant includes at least one of rhodamine B, methylene blue, and methyl orange dyes.
Citation Information
Patent Citations
WS2 / MoS2 two-dimensional coherent heterojunction network material and preparation method thereof
CN114709137A
Rare earth La anchored WS2 / WO3-x heterojunction photocatalytic material as well as preparation method and application thereof
CN117943061A
Hydro-thermal preparation method of plate tungsten disulfide nano sheet
CN108178195A
Cited By
Preparation method and application of LiNbO3 / g-C3N5 heterojunction composite photocatalyst
CN122787051A